Structural impairment and conflict load as vulnerability factors for burnout – A cross-sectional study from the German working population - Perlinger, Julia; Gisch, Hannes; Ehrenthal, Johannes C.; Montag, Christiane; Kretschmar, Thomas (Frontiers in Psychology, 2023)
Individual vulnerability and resilience factors are increasingly studied in burnout research. This is especially true for clinical variables that translate directly into intervention programs from a psychodynamic perspective. For example, few studies have examined the relationship between structural impairment and the individual spectrum of motivational conflicts according to the Operationalized Psychodynamic Diagnosis system (OPD) in relation to burnout. To substantiate previous findings, we hypothesized that structural impairment as well as motivational conflicts are related to burnout, but that structural impairment explained additional variance and mediated a possible relationship between conflicts and burnout. The present cross-sectional study was carried out on a sample representative of the German working population (N = 545). Questionnaires were used to measure structural impairment (OPD-SQS), the conflict-modes as well as the category K0 (OPD-CQ), and burnout (BOSS-I/-II). Structural impairment, a number of conflict modes, and burnout were significantly associated. Moreover, structural impairment explained additional variance in burnout. The requirements for the conflict-specific mediation models were given for 9 of the 12 OPD conflict modes. In these models the impact of the conflict modes on burnout was mediated by structural impairment.